2021
DOI: 10.1177/0956462420987435
|View full text |Cite
|
Sign up to set email alerts
|

HIV care cascade among cisgender men who have sex with men in a key population-led community center in the Philippines

Abstract: The HIV epidemic in the Philippines is the fastest growing globally, and disproportionately affects cisgender men who have sex with men (cis-MSM) demanding effective strategies for this key population (KP) group. KP-specific and community-based (CB) interventions have improved the HIV response elsewhere, but these have yet to be evaluated locally. We analyzed the HIV care cascade outcomes in a KP-led, CB HIV test-and-treat center and determined factors that affect these by performing a retrospective study of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…with an opportunistic infection (OI)] or symptomatic, during the late stages of their illness. However, a recently published study [ 13 ] among young cis-MSM in a community-based treatment hub, also showed that a good proportion (35%) of newly diagnosed cases in their cohort presented with advanced HIV disease. This suggests that similar factors in both community- and hospital-based hubs played a role in the delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with an opportunistic infection (OI)] or symptomatic, during the late stages of their illness. However, a recently published study [ 13 ] among young cis-MSM in a community-based treatment hub, also showed that a good proportion (35%) of newly diagnosed cases in their cohort presented with advanced HIV disease. This suggests that similar factors in both community- and hospital-based hubs played a role in the delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…looked at the care cascade outcomes among MSM in a key population-led, community-based, HIV test-and-treat center in Metro Manila. They found that they achieved higher rates than national outcomes as 78% initiated ART and 84% achieved VL suppression in their center [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HIV epidemic in the Philippines is one of the fastest growing epidemics globally, with 207% increase in new HIV infections and 388% increase in AIDS deaths from 2010 to 2020. In 2020, an estimated 73% of people living with HIV in the Philippines knew their status and 44% of people living with HIV were on antiretroviral therapy (ART) [ 1 - 4 ]. In 2 studies of cohorts of patients with HIV in Manila, 84% to 90% of patients who started ART had achieved viral suppression [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, an estimated 73% of people living with HIV in the Philippines knew their status and 44% of people living with HIV were on antiretroviral therapy (ART) [ 1 - 4 ]. In 2 studies of cohorts of patients with HIV in Manila, 84% to 90% of patients who started ART had achieved viral suppression [ 4 , 5 ]. Most new and existing HIV infections occur among men who have sex with men (MSM) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the established linkages between migration and health (Thomas et al, 2019) and the paucity of knowledge about Asian gay and bisexual men, this research focuses on Filipino gay and bisexual men as members of the rapidly growing Filipino new settler group. This focus is also appropriate due to the Philippines experiencing a fast-growing HIV epidemic, particularly among men who are having sex with other men (Adia et al, 2020; Eustaquio et al, 2021; Gangcuangco, 2019; Restar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%